2019
DOI: 10.1093/jcr/ucz052
|View full text |Cite
|
Sign up to set email alerts
|

Love, Lies, and Money: Financial Infidelity in Romantic Relationships

Abstract: Romantic relationships are built on trust, but partners are not always honest about their financial behavior—they may hide spending, debt, and savings from one another. This article introduces the construct of financial infidelity, defined as “engaging in any financial behavior expected to be disapproved of by one’s romantic partner and intentionally failing to disclose this behavior to them.” We develop and validate the Financial Infidelity Scale (FI-Scale) to measure individual variation in consumers' financ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 61 publications
2
36
0
Order By: Relevance
“…By systematically contrasting the mediating roles of one’s level of dependence, mutuality of dependence, and overlapping interests, future research might be able to identify the explanatory power of these various drivers. Future research could also explore which facets of relationship quality (e.g., trust, passion, intimacy; Fletcher et al, 2000) benefit the most from account pooling, and examine the downstream effects on financial behaviors, such as financial infidelity proneness (Garbinsky et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…By systematically contrasting the mediating roles of one’s level of dependence, mutuality of dependence, and overlapping interests, future research might be able to identify the explanatory power of these various drivers. Future research could also explore which facets of relationship quality (e.g., trust, passion, intimacy; Fletcher et al, 2000) benefit the most from account pooling, and examine the downstream effects on financial behaviors, such as financial infidelity proneness (Garbinsky et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In this spirit, our research offers new insights on gift giving to two research areas, ethical decision making and interpersonal relationships. There is a growing research stream on interpersonal, romantic relationships in decision making (especially joint decision making; Garbinsky et al, 2020; Kardas et al, 2018; Liu et al, 2019; Tu et al, 2016). Here, we highlight the potential unintended consequences of a particular type of decision on such relationships.…”
Section: Discussionmentioning
confidence: 99%
“…A primary driver of this shift in purchasing behavior is feeling the need to justify purchase decisions when financial resources are shared (Garbinsky & Gladstone, 2019). Indeed, Garbinsky et al (2020) showed that when members of couples are lower in financial harmony, they are more likely to have some resources, such as credit cards or bank accounts, that are concealed rather than fully shared.…”
Section: Individual Decisions Influenced By Close Othersmentioning
confidence: 99%